Отримання культури «бородатих» коренів полину звичайного з геном ifn-α2b людини - Дробот, К.О.; Шаховський, А.М.; Матвєєва, Н.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. The obtaining of mugwort Artemisia vulgaris L. “hairy” root culture with human interferon б2b gene (ifn-α2b) was
the aim of this work. Methods. We used Agrobacterium rhizogenes wild strain A4 as well as A. rhizogenes carried pCB161
vector with ifn-α2b gene under constitutive Mll rootspecific sugar beet promoter for mugwort genetic transformation. The
genes were transferred into leaf and root explants. The presence of transgenes were determined by PCR analysis. Results.
Transformation frequency was up to 100 % in case of leaf explants. Transgenic roots from other type of explants were
not obtained. PCR analysis proved the presence of nptII, ifn-α2b and rolB genes in mugwort “hairy” roots obtained via
A. rhizogenes-mediated transformation. Conclusions. Thus, we obtained the transgenic Artemisia vulgaris L. “hairy” roots
using A. rhizogenes-mediated transformation and transferred ifn-α2b. Transformational frequency was the highest in case of
leaves using as an explants – up to 100 %.
Keywords: genetic transformation, Agrobacterium rhizogenes, hairy roots, Artemisia vulgaris L., ifn-α2b gene.